Production of Marker-Free Apple Plants Expressing the Supersweet Protein Gene Driven by Plant Promoter - Timerbaev, Vadim; Mitiouchkina, Tatiana; Pushin, Alexander; Dolgov, Sergey (Frontiers in Plant Science, 2019)
The presence of antibiotic resistance and other marker genes in genetically modified plants causes concern in society because of perceived risks for the environment and human health. The creation of transgenic plants that do not contain foreign genetic material, especially that of bacterial and viral origin, largely alleviates the tension and makes the plants potentially more attractive for consumers. To produce marker-free transgenic apple plants, we used the pMF1 vector, which combines Zygosaccharomyces rouxii recombinaseR and a CodA-nptII bifunctional selectable gene. The thaumatin II gene from the tropical plant Thaumatococcus daniellii, which is under the control of the plant E8 gene (a predominantly fruit-specific promoter) and rbsS3A terminator, was taken as the gene of interest for modification of the fruit taste and enhancing its sweetness. Exploitation of this gene in our laboratory has allowed enhancing the sweetness, as well as improving the taste characteristics, of fruits and vegetables of plants such as strawberry, carrot, tomato and pear. We have obtained three independent transgenic apple lines that have been analyzed by PCR and Southern blot analyses for the presence of T-DNA sequences. Two of them contained a partial sequence of the T-DNA. With one line containing the full insert we then used a delayed strategy for the selection of marker-free plants. After induction of recombinase activity in leaf explants on selective media with 5-fluorocytosine we obtained more than 30 sublines, most of which lost their resistance to kanamycin. Most of the apple sublines showed the expression of the supersweet protein gene in a wide range of levels as detected by RNA accumulation. The plants from the group with the highest transcript level were propagated and grafted onto dwarf rootstocks for early fruit production for future estimates of protein levels and organoleptic analyses. Thus, we developed a protocol that allowed the production of marker-free apple plants expressing the supersweet protein.